2016
DOI: 10.1093/jxb/erw099
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance plant signaling pathways in response to multiple stressors: the gap in knowledge

Abstract: Plants require the capacity for quick and precise recognition of external stimuli within their environment for survival. Upon exposure to biotic (herbivores and pathogens) or abiotic stressors (environmental conditions), plants can activate hydraulic, chemical, or electrical long-distance signals to initiate systemic stress responses. A plant's stress reactions can be highly precise and orchestrated in response to different stressors or stress combinations. To date, an array of information is available on plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
158
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(164 citation statements)
references
References 207 publications
4
158
0
2
Order By: Relevance
“…Three types of plant signals (chemical, hydraulic and electrical) are known to regulate stomatal behavior in response to internal and external stimuli such as changes in atmospheric relative humidity and soil moisture, yet signal integration is highly complex and not well-understood (e.g. Huber & Bauerle, 2016). In various systems, each of these three signal types has been proposed as the primary contributor to stomatal closure (Zhang & Davies, 1989;Fromm & Eschrich, 1993;Christmann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Three types of plant signals (chemical, hydraulic and electrical) are known to regulate stomatal behavior in response to internal and external stimuli such as changes in atmospheric relative humidity and soil moisture, yet signal integration is highly complex and not well-understood (e.g. Huber & Bauerle, 2016). In various systems, each of these three signal types has been proposed as the primary contributor to stomatal closure (Zhang & Davies, 1989;Fromm & Eschrich, 1993;Christmann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the events leading to jasmonate accumulation distal to the wound (systemic response) can be reduced by two principal mechanisms: the transport of jasmonates between cells (cell‐nonautonomous pathway typical for family Solanaceae; Schilmiller & Howe, ; Wasternack et al ., ) and a rapid electrical, hydraulic or chemical signal that triggers JA synthesis in distal leaves (autonomous pathway typical for the model plant Arabidopsis , Glauser et al ., ; Koo et al ., ; Koo & Howe, ; Mousavi et al ., ; Farmer et al ., ; Gaupels et al ., ). Moreover, both pathways may work synergistically to optimize the spatial and temporal expression of defence responses (Koo & Howe, ; Huber & Bauerle, ). However, a recent study has demonstrated the importance of electrical signalling in long‐distance communication in Arabidopsis (Mousavi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The results implied that genotype rankings across environments changed due to the variation in correlation between the genotype and phenotype, making it difficult to select superior genotypes across environments thus most genotype recommendations would be made for specific environments. Metabolite variances have been reported to occur due to plants detecting and responding to specific environmental signals via various pathways including increase in antioxidative capacity (Huber & Bauerle, 2016). Similar results were reported in wheat where genotype and environment were significantly affecting flavonoid, phenolic and antioxidative capacity (Shamloo et al, 2017).…”
Section: Stability Performance Of the Genotypes Environmental Factormentioning
confidence: 59%